Advances in Regenerated Asphalt Mixtures - Li, Yuanyuan; Bai, Tao; Zhang, Jizhe; Gao, Yangming (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The recycling of asphalt mixtures has significant contributions towards the reduction in greenhouse gases, pollution, natural resources, and energy consumption. Sustainable road materials and technologies can provide a powerful boost to "carbon-neutral strategies", and so it is crucial to continue moving towards improving these technologies and theories.This Special Issue includes new findings in the field of regenerated asphalt mixtures, including the high-content regeneration of RAP, cold recycling technologies, regenerated mechanisms, eco-regenerating agents, and anti-aged materials. Additionally, novel materials, fast maintenance technologies, and functional materials are also addressed in this Special Issue, such as bio-asphalt materials, intelligent transportation, self-healing technologies, solid waste resource applications, numerical simulations, smart road materials and technologies, etc.